Análise de sistemas OFDM cooperativos AF com amplificadores de potência não lineares - Farias, Éder Jacques Porfírio (2013)
Cooperation diversity and orthogonal frequency division multiplexing (OFDM) are two key technologies for the modern wireless communication systems. The cooperative communication systems considered through this work use the OFDM technology and they are composed of: one transmitter with a nonlinear power amplifier (PA), one or more amplify-and-forward (AF) relays, also having a nonlinear PAs, and one destination node. In this dissertaion, it is initially proposed an optimal receiver, in the signal to noise ratio (SNR) sense, for a nonlinear cooperative AF system. The proposed receiver uses the maximum ratio combining (MRC) diversity technique to combine the received signas, assuming that both the source-destination and source-relay-destination links are available. In the sequel, closed-form expressions for the instantaneous SNR and outage probability of the considered system are developed. The outage analysis is then extended to the case of a multi-hop system, that is, with multiple serial relays. Finally, an outage analysis is also proposed for a nonlinear AF OFDM system using a Selection Combining receiver, considering two cases: one relay and multiple parallel relays. Numerical simulation results are presented through the work, evaluating the performance of the proposed receiver and theoretical expressions.